Peran knowledge retention repository dalam pemenuhan kebutuhan informasi mahasiswa jurusan kebidanan di Perpustakaan Poltekkes Kemenkes Surabaya - Naila Sankrisza (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study examines the utilization of the knowledge retention repository in fulfilling the information needs of midwifery students at Poltekkes Kemenkes Surabaya. Higher education libraries have shifted their role not only as providers of book collections but also as centers of knowledge management that support academic, research, and professional practice activities. For midwifery students, access to accurate, up-to-date, and relevant information is crucial to support both theoretical learning and clinical practice. The purpose of this research was to describe the extent of repository utilization, analyze the information needs that can be met through repository services, and identify its contribution to academic information services. This research employed a quantitative descriptive method with a sample of 100 midwifery students selected through purposive sampling. Data were collected using a questionnaire developed based on indicators of information needs and repository utilization, then analyzed using descriptive statistics. The findings show that the repository is effective in providing relevant and well-organized collections, with indicators of collection availability, knowledge management, and accessibility rated high. However, challenges remain in terms of long-term storage sustainability and speed of access, which received lower scores compared to other indicators. Overall, the repository significantly supports students’ academic information needs, enhances learning effectiveness, and promotes systematic knowledge dissemination. It is concluded that strengthening digital infrastructure, improving long-term preservation policies, and optimizing system access are necessary to ensure the sustainability and efficiency of repository utilization for midwifery education.